IDENTIFIKASI KEBUTUHAN PRASARANA KEGIATAN BELAJAR SISTEM TATAP MUKA MASA PANDEMI DI SMA TRIGUNA - Nina Carina; Mekar Sari Suteja (PROSIDING SERINA, 2021)
The COVID-19 pandemic has changed all aspects of life. In the education system, to avoid and prevent the transmission of the Covid-19 virus, the government has established an online learning system (on the network), as a learning system that eliminates direct meetings between students and teachers in school buildings. However, the system cannot be separated from all the shortcomings and problems it causes. With the decline in new daily cases, cases of death due to Covid-19, and vaccinations for people aged 12-17 years, the government has obligated schools to reopen direct learning (PTM) in a limited way. Triguna High School has volunteered to be one of the first schools to implement Limited Direct Learning in DKI Jakarta. To obtain limited PTM,  SMA Triguna must meet several requirements. Through discussions, interviews, field identification, the PKM team helps SMATriguna to identify the completeness of those requirements. As a final result, the PKM Team helped SMA Triguna to design two types of information boards, namely the school information board as a place to attach formal information, and the class information board to attach information related to the class activity. Class information boards are made in a special design to arouse the enthusiasm for learning and achievement of Triguna High School students when limited PTM is carried out. The selection of shapes, colors, and materials is used as a consideration in realizing creativity. The existence of an information board is not only needed for disseminating information related to activities, health conditions, and other information, but also a fulfillment of one of the requirements for achieving A accredited SMA Triguna.